(3GdhGaj aj TQM fXGe GdeQGaYGJ GdTQYjI GdSYhOj habkG dCMOKs - (3GdSjO YHO GdHGSW, YeGQ,s ((3GdeedcI GdYQHjI GdSYhOjI (B:s, 2025)
This work offers a comprehensive commentary on the Saudi Arabian Law of Sharia Litigation Procedures, examining its articles in detail while clarifying the procedural rules governing civil litigation before Saudi courts. The author addresses the latest legislative amendments to the law and its executive regulations, making this an essential reference for judges, legal practitioners, and researchers specializing in Saudi procedural law. (3jJfGhd gPG GdcJGH TQMkG hGajkG hJMdjdkG eYebkG dfXGe GdeQGaYGJ GdTQYjI aj GdeedcI GdYQHjI GdSYhOjI, EP jSJYQV GdeDda CMcGe GdfXGe eGOkI eGOkI eY HjGf GdbhGYO GdELQGFjI GdefpqXeI ddJbGVj CeGe GdeMGce GdSYhOjI, hojYfi HEHQGR BNQ GdJYOjdGJ GdJTQjYjI GdhGQOI Ydjg, eY GdETGQI Edi GddhGFM GdJfajPjI PGJ GdUdI, eeG jLYdg eQLYkG CSGSjkG ddbVGI hGdeMGejf hGdHGMKjf GdbGfhfjjf(B.s
(3GdfU HGdYQHjI(B.s
Keywords: (3bGfhf GdeQGaYGJs -- (3GdeedcI GdYQHjI GdSYhOjI(B.s; (3GdELQGAGJ GdbVGFjIs -- (3GdeedcI GdYQHjI GdSYhOjI(B.s; (3GdeedcI GdYQHjI GdSYhOjIs -- (3bGfhf hfXGe(B.s; Print books